Editors’ Introduction: Margins, Moral Authority, and the Work of Social Change - Asep Iqbal (Journal of Asian Social Science Research, 2020)
The JASSR Vol. 2, No. 1 (2020) presents a reflection on marginalization, moral authority, and social change across Asia and the Global South. The issue brings together studies on Roma marginalization in post-communist Bulgaria, grounded Islamic feminism in Indonesia, liberal-progressive Muslim reformism, Sasak anti-colonial resistance in Lombok, and debates over top-down and bottom-up development. Together, the articles show how communities respond to exclusion not only through suffering, but also through reinterpretation, activism, resistance, and institutional negotiation. The issue highlights social science’s capacity to recover voices from the margins and to examine how more dignified and inclusive futures are imagined.